Menjembatani Penelitian Kualitatif dan Kuantitatif Irfan Sanusi - Sanusi, Irfan (Jurnal Ilmu Dakwah, 2009)
The quantitative method of research inspired by August Comte in his Philosophy of Positivism, is contradictory with the qualitative method of research which is one of the methods elaborated and derived fromÂ  rationalism. I suggest that quantitative researchÂ  modelsâ descriptive model, correlation, experiment and quasi-experiment â should be placed on the grand theory as well as the the social context, or to follow the logic of qualitative method, so thatÂ  research invention is inseparable from the grand situation. In light of this view, IÂ  suggest that theÂ  two contradictory methods of research be combined.